비-포스터 회로가 결합된 UHF 대역 CRLH 전송선 안테나 설계 - 이종협; 이용혁; 최성로; 정재영; 박용배 (한국전자파학회 논문지, 2019)
In this paper, we propose an ultra high frequency(UHF) band military antenna using composite right/left handed(CRLH) transmission lines and non-Foster circuits. The antenna uses the zeroth-order characteristic of the CRLH transmission line in order to miniaturize the antenna. The non-Foster circuit’s negative capacitance can offset the input reactance of the antenna to improve bandwidth. The size of the CRLH transmission line antenna is 20.9×13.2×1.6 mm3 and the size of the non-Foster circuit is 20×14.4×1.6 mm3. The measured received power of the antenna is improved by an average of 19.96 dB at 250～500 MHz.
Keywords: Composite Right/Left-Handed Transmission Lines; Non-Foster Circuit; Military Antenna; UHF Band Antenna